PENGARUH LABA BERSIH DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM : Pada Perusahaan Indeks LQ-45 yang Terdaftar di Bursa Efek Indonesia - Widya Lestari; Zulfa Rosharlianti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine and empirically prove the effect of net income and operating cash flow on stock returns in LQ-45 Index Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The LQ-45 Index Company is one of the stock indexes consisting of 45 companies with good fundamentals and corporate liquidity. This type of research is quantitative research. The population in this study are all LQ-45 Index Companies listed on the Indonesia Stock Exchange in 2017-2021 as many as 45 companies (observations in 2021). The sample selection method selected was purposive sampling and obtained a sample of 13 companies with a period of 5 years of research, so the observation data were 65 data. The results of the study simultaneously state that net income and operating cash flow have a significant effect on stock returns. The results of the study partially stated that net income had no effect on stock returns and operating cash flow had no effect on stock returns